The development of public accounting transparency in selected Arab countries. (June 2014) - Abushamsieh, Khalil; López-Hernández, Antonio M.; Ortiz-Rodríguez, David
The aim of this article is to analyse the level of public financial information disclosed by certain Arab countries in the Middle East, in view of calls for greater transparency and international trends in this respect. Accordingly, we examined the financial reports published online by the selected countries, contrasting them with the financial statements and contents proposed in the International Public Sector Accounting Standards (IPSAS) issued by the International Federation of Accountants. The results show that the Arab countries analysed present a low level of public financial information. They all present similar degrees of compliance with IPSAS 1 and 2. Nonetheless, we can observe that aid-receiving countries are implementing the policies stipulated in the international recommendations in response to the demands of donors and international agencies. Countries with oil revenues experience less pressure to implement the IPSAS. Points for practitioners: The findings of this article may be of interest to public managers in all the selected Arab countries, especially those in the public administrations of the Gulf Cooperation Council countries and to consulting companies in the Gulf region. The analysis made of financial legislation and of the IPSAS 1 and 2 indexes for the selected countries may encourage them to initiate a process of financial reforms.